Agitación y transferencia de masa de CO2 en fotobiorreactores tipo airlift (2017)
The production of biomass from microalgae in closed systems such as photobioreactors is a function of different issues: substrate concentration, pH, temperature, aeration and agitation of the growth medium; the latter is one of the most important elements because it has a direct influence on mass transfer. The impact of this factor on the design of photobioreactors is the object of study in this article. With the support of the bibliographic review, it found that the agitation that disperses the CO2, affects the number of bubbles, the retention of gas and the diameter of the bubble. These conditions, for mass production developed in photobioreactors directly, have an impact on the design, for which photobioreactors type airlift have been generated, that proposes, as a first step, increasing the retention of gas whilst decrease the relation of areas on the equipment and as a second step, promoting the transfer of mass regarding the handling of bubble sizes that increase the contact area between the gas-liquid phases. These patterns for the design of the airlift photobioreactors seek to carry out the mass transfer to appropriate values.